The influence of seat height, trunk inclination and hip posture on the activity of the superior trapezius and longissimus - Bertolaccini, Guilherme da Silva [UNESP]; Nakajima, Rafael Kendi [UNESP]; de Carvalho Filho, Idinei Francisco Pires [UNESP]; Paschoarelli, Luis Carlos [UNESP]; Medola, Fausto Orsi [UNESP] (Society of Physical Therapy Science, 2016)
[Purpose] This study was aimed at investigating the influence of seat height and body posture on the activity of the superior trapezius and longissimus muscles. [Subjects and Methods] Twenty two healthy subjects were instructed to perform a total of eight different body postures, varying according three main factors: seat height (low and high seat); trunk inclination (upright and leaning forward at 45°); and the hips in abduction and adduction. Electromyography of the superior trapezius and longissimus was collected bilaterally, and the average values were obtained and compared across all the postures. [Results] The activity of the superior trapezius and longissimus significantly changes according to the seat height and trunk inclination. For both seat heights, sitting with trunk leaning forward resulted in a significant increase in the activity of both muscles. When sitting in a high seat and the trunk leaning forward, the superior trapezius activity was significantly reduced when compared to the same posture in a low seat. [Conclusion] This study contributes to the knowledge on the influence of the body posture and seat configuration on the activity of postural muscles. Reducing the biomechanical loads on the postural muscles must be targeted in order to improve users’ comfort and safety.
Keywords: Electromyography; Posture; Seat